Single‐Crystal ZnO/AlN Core/Shell Nanowires for Ultraviolet Emission and Dual‐Color Ultraviolet Photodetection. Issue 6 (8th January 2019) - You, Daotong; Xu, Chunxiang; Zhao, Jie; Qin, Feifei; Zhang, Wei; Wang, Ru; Shi, Zengliang; Cui, Qiannan
Abstract: Core–shell nanostructures can combine the advantages of different functional materials to realize property tunability and enhance optical and optoelectrical performance. Here, vertically aligned ZnO/AlN core/shell nanowires have been facilely fabricated by sputtering AlN layer onto the ZnO nanowires grown by vapor phase transport. The morphological and structural characterization reveals that single‐crystal AlN shell layer with thickness of ≈15 nm is coated uniformly on the single‐crystal ZnO nanowire with diameters of ≈330 nm. The core/shell nanowire exhibits 24 times enhancement of ultraviolet emission and quenching of the deep level emission from ZnO. Moreover, under ultraviolet irradiation (325 nm), the photodetector based on the core/shell nanowire displays higher photoresponsivity (from 3.8 × 10 3 to 2.05 × 10 4 A W −1 ), faster response speed (from 397 to 28 ms), and higher I 325nm / I dark ratio (from 453 to 1.1 × 10 4 ) than that bare ZnO nanowire device. Under the vacuum ultraviolet (193 nm) illumination, the I 193nm /Idark ratio and photoresponsivity are 300 and 381 A W −1, respectively. In one word, this paper employs a facile and general technique to solve a challenging fabrication issue, and obtains perfect crystal core/shell structure with high performance for ultraviolet emission and detection. Abstract : This paper employs a facile and general technique combining vapor phase transport with sputtering to solve a challenging fabrication issue, and obtains perfect crystal ZnO/AlN core/shell structure with dramatic enhancement of ultraviolet emission up to 24 times. Moreover, the core/shell nanowire device shows dominant photoresponses at ultraviolet (325 nm) and vacuum‐ultraviolet (193 nm) regions.